2013
DOI: 10.1074/jbc.m112.438440
|View full text |Cite
|
Sign up to set email alerts
|

NADPH:Quinone Oxidoreductase 1 Regulates Host Susceptibility to Ozone via Isoprostane Generation

Abstract: Background: NQO1 regulates pulmonary susceptibility to ozone. Results: In NQO1-null mice, ozone exposure generates precursors of A 2 -isoprostane in the lung. A 2 -isoprostane suppresses ozone-induced IL-8 expression, inhibits NF-B, and modifies Cys 179 in IKK. Conclusion: A 2 -isoprostane inhibits ozone-induced NF-B activation via IKK inhibition. Significance: This molecular mechanism explains the paradoxical observation that loss of NQO1 protects from ozone toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
(63 reference statements)
0
3
0
Order By: Relevance
“… 46 , 47 This gene is a member of the NAD(P)H dehydrogenase (quinone) family and encodes a cytoplasmic 2-electron reductase which reduces quinones to hydroquinones. Lower NQO1 activity caused by gene mutations has been associated with tardive dyskinesia, 48 an increased pulmonary susceptibility to ozone, 49 and susceptibility to various forms of cancer. 50 , 51 In addition, NQO1 binds and protects the tumor suppressor p53 against proteasomal degradation; thus, it has even broader cytoprotective roles, beyond its enzymatic functions.…”
Section: Review Of Genes and Results For Degenerative And Immunologicmentioning
confidence: 99%
“… 46 , 47 This gene is a member of the NAD(P)H dehydrogenase (quinone) family and encodes a cytoplasmic 2-electron reductase which reduces quinones to hydroquinones. Lower NQO1 activity caused by gene mutations has been associated with tardive dyskinesia, 48 an increased pulmonary susceptibility to ozone, 49 and susceptibility to various forms of cancer. 50 , 51 In addition, NQO1 binds and protects the tumor suppressor p53 against proteasomal degradation; thus, it has even broader cytoprotective roles, beyond its enzymatic functions.…”
Section: Review Of Genes and Results For Degenerative And Immunologicmentioning
confidence: 99%
“…The protocol was approved by the Institutional Review Board for clinical investigations, Duke University Medical Center to use deidentified human lung donor airway tissue discarded during lung transplant procedure. Primary HBE cells were harvested and cultured as previously described ( 50 , 51 ). Briefly, human tracheobronchial tissues obtained from the Lung Transplant Program in the Department of Pathology at Duke University Medical Center were processed by proteolytic digestion (Protease Type XIV, Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Gene polymorphisms for the phase-II xenobiotic metabolizing enzyme NQO1 have been allied to pulmonary and epithelial impairments in response to O 3 in the exercising subjects (Bergamaschi et al, 2001;Kummarapurugu et al, 2013). NQO1 Pro187Ser polymorphism was evaluated in a study on nitrogen dioxide and its effects on asthma, which showed a recessive effect for the 187 Pro/Pro genotype (Castro-Giener et al, 2009).To assess the functional significance and potential impact of this mutation on the structure of NQO1 protein, a bioinformatics based approach was pursued to perform the sequence and structural analysis of this protein.…”
Section: Accepted Manuscriptmentioning
confidence: 99%